Femoral neck rotational osteotomy for femoral head osteonecrosis ficat arlet stage III: A Case Report - Putra, Satria Prawira; Mulyadi, Dicky (The Hip and Knee Journal, 2023)
Peritrochanter osteotomy for treatment AVN head femur has a techinacally demanding because excecsive rotation would tighten the retinaculum that contain blood supply for proximal femur and most complication is non union greater trocanter.based on this point of view,the retinaculum was release during surgery and rotational osteotomy was performed at the based of femoral neck